Students’ Learning Perception in Using the English for Nusantara Textbook at Junior High School - Nanda Nurlaila; Meristika Moetia (Universitas Islam Negeri Palopo, 2026)
This study explored students' perceptions of the use of the English for Nusantara textbook at Junior High School Ibnu Sina. Employing a qualitative approach, data were collected through semi-structured interviews with 12 eighth-grade students and analyzed using thematic analysis with the support of NVivo 12 software. The findings revealed four major themes, included students' overall perceptions of the textbook, textbook design and learning activities, textbook support for learning English, and challenges encountered while using the textbook. Overall, most students expressed positive impression, describing the textbook as interesting, engaging, and helpful for learning English. The visual illustrations and task-based activities in textbook enhanced students' motivation and classroom engagement. Furthermore, students perceived that the textbook supported their vocabulary development, helped them understand English materials more easily, and encouraged them to practice speaking and writing through contextual learning activities. Nevertheless, students also reported several challenges, including unfamiliar vocabulary, the need for teacher guidance, and some illustrations that were perceived as unclear or less supportive. These findings suggest that while English for Nusantara effectively supports the implementation of the Merdeka Curriculum through communicative and contextual learning, teachers continue to play a crucial role in providing scaffolding and adapting instruction to accommodate students' diverse learning needs.